Reversible nano-crack film and preparation method and application thereof
By depositing tellurium film on the PMN-PT ferroelectric single crystal substrate and applying a pulse electric field to induce ferroelectric domain flip, forming a reversible nanocrack film, the problems of low efficiency and high energy consumption of memory devices are solved, and high efficiency and low power consumption are achieved memory device.
Patent Information
- Application Number
- CN202411535252.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
AI Technical Summary
Existing memory devices have problems of inefficiency and high energy consumption in data transmission and processing, especially due to the 'memory wall' limitations caused by the von Neumann architecture, requiring a new type of nonvolatile memory to increase read speed and Reduce power consumption.
A 50nm-thick tellurium film was deposited on a PMN-PT ferroelectric single crystal substrate, and a 109° ferroelectric domain flip was induced by applying a pulsed electric field to form a reversible nanocrack film. The film achieves dynamic, reversible, non-volatile resistance control through electric field regulation, achieving low power consumption and high on/off ratio effects.
The preparation of high-quality Te/PMN-PT heterojunction is realized, and the extremely large non-volatile regulation is achieved through electric field regulation, achieving static power consumption close to zero, with excellent stability and fatigue resistance, suitable for new types Development of nonvolatile memory.
Smart Images

Figure CN119433459A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a reversible nanocrack film, in particular to a reversible nanocrack film and a preparation method and application thereof, belonging to the technical field. Background Art
[0002] With the development of big data, artificial intelligence, and the Internet of Things, consumer electronics products such as mobile phones and computers are increasingly in need of high-quality, high-computing speed, high-density, and low-power chips to cope with the growing needs of data processing and storage. Therefore, it is urgent to accelerate the development of new memory that can both increase computing speed and reduce energy consumption.
[0003] At present, when computers based on the von Neumann architecture perform calculations, data must be repeatedly transferred between the computing unit (CPU or GPU) and the memory, which limits the overall efficiency and computing time, and causes a large amount of energy consumption, resulting in the so-called "memory wall". In order to overcome the limitations brought by the "memory wall" and improve computing performance, it is very necessary to make the memory more closely integrated with computing resources.
[0004] Therefore, it is particularly important to build a new type of non-volatile memory with low power consumption, high reading speed and integrated visual sensing and signal processing.
[0005] With the development of ferroelectric materials, people have begun to try to apply high-performance ferroelectric materials to fields such as memory. Since ferroelectric devices have the advantages of non-volatility, fast reading speed and low power consumption, they are considered to be a new type of non-volatile memory with great application prospects.
[0006] Compared with devices with a single ferroelectric layer as the core component, devices with functional thin film / ferroelectric heterojunction as the core structure have the advantages of non-destructive reading, high storage density, and multi-functions. By applying an external electric field to the thin film / ferroelectric heterojunction, the electrical, magnetic, and optical properties of the functional device can be controlled by using ferroelectric materials as the gating medium.
[0007] Applying an electric field to a thin film / ferroelectric heterojunction usually produces two control mechanisms: lattice strain effect and interface charge effect. The inverse piezoelectric effect in the ferroelectric layer causes in-plane strain, which is then transmitted to the thin film layer, causing changes in its lattice strain-related physical properties. This control mechanism is called the lattice strain effect. On the other hand, when the polarization direction in the ferroelectric substrate is reversed, the polarization charge on the substrate surface attracts or repels the carriers of the thin film to the interface, thereby changing the carrier concentration in the film and its related electrical properties. This is the interface charge effect, also known as the ferroelectric field effect. However, the control amplitude produced by the lattice strain effect is small, the ferroelectric field effect has high requirements on the preparation process of the thin film, and both effect devices have static power consumption, which is not conducive to practical applications. Summary of the invention
[0008] To address the deficiencies of the prior art, the present invention aims to provide a reversible nanocrack film.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A reversible nanocrack film is a tellurium film with a thickness of 50nm deposited on a PMN-PT (001) ferroelectric single crystal substrate. The electric field induces 109° ferroelectric domain flipping, causing the nanocracks on the surface of the tellurium film to reversibly open and close.
[0011] The electric field strength is E G =Pulsed electric field of ±2kV / cm.
[0012] A method for preparing a reversible nanocrack film comprises the following steps: a pulsed laser precipitation method is used to deposit and grow a tellurium film on a PMN-0.29PT ferroelectric single crystal substrate to form a reversible nanocrack film with a "Te film / PMN-0.29PT" structure.
[0013] The size of the PMN-0.29PT ferroelectric single crystal substrate is 5 mm×5 mm×0.5 mm; the laser energy density of the pulsed laser precipitation method is 1.5 J / cm 2 ; The deposition temperature is 140°C and the deposition pressure is 1×10 -5 Pa.
[0014] The above-mentioned reversible nanocrack film is used as a nanocrack switch.
[0015] The above-mentioned nanocrack switch is used in non-volatile memory.
[0016] The present invention is beneficial in that:
[0017] A reversible nanocrack film of the present invention uses a pulsed laser deposition method to prepare a high-quality Te / PMN-PT heterojunction. By applying an electric field parallel to the thickness direction of PMN-0.29PT (001), the electrical properties and surface morphology of the heterojunction are studied, and the effect of thickness on the electrical properties and surface morphology of the heterojunction is studied in depth, and the following experimental results are obtained:
[0018] (1) An external electric field drives the 109° ferroelectric domain flipping of the ferroelectric single crystal to form an electrically controlled reversible nanomechanical crack on the surface of the Te film. The opening and closing of the crack realizes the dynamic, reversible, and non-volatile control of the film's resistance state. When the crack is open, the film is approximately equivalent to an open circuit state, so that the film is in a standby state with a power of nearly 0, and the on-off ratio reaches 3.6×10 6 .
[0019] (2) Even if more than 10 3 After the first cycle, the ON and OFF states also remain stable for more than 6 hours, which shows that the device has excellent stability and fatigue resistance. Using this unique structure, a new framework for ferroelectric memory devices can be designed, which is characterized by high on / off ratio, ultra-low power consumption and superior stability.
[0020] (3) The thinner the film, the larger the R(ON) / R(OFF) value. As the thickness increases, the cracks on the film surface become more and more blurred. As the film becomes thicker, it becomes increasingly challenging to transfer the in-plane tensile strain in the PMN-PT layer to the film surface. Therefore, when the film becomes thicker, the resistance in the negative polarization state and the on-off ratio will decrease.
[0021] A reversible nanocrack film of the present invention provides a new idea and method for realizing the regulation of heterojunction performance by electric field. Under the action of electric field, nanocracks extend from the ferroelectric layer into a specific film, and during the period of opening, air gaps are formed between the electrodes, and the film is close to being short-circuited. When the direction of the electric field changes, the crack changes from an open state to a closed state, and the film resistance is significantly reduced. Electric field controllable cracks can not only achieve extremely large amplitude and non-volatile regulation, but also because the film is close to being short-circuited when the crack is opened, it can achieve near-zero static power consumption, which well meets the low power consumption requirements of the device, and has strong practicality and wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of spark plasma sintering device.
[0023] Figure 2 This is the XRD diffraction pattern of Te powder.
[0024] Figure 3 GIXRD 2θ scans of Te films at different deposition temperatures.
[0025] Figure 4 Surface AFM morphology images of Te films at different deposition temperatures.
[0026] Figure 5 Schematic diagram of the internal polarization direction of PMN-0.29PT when the substrate is in positive and negative polarization states (Figures ab).
[0027] Figure 6 The resistance curve of Te film grown at different deposition temperatures (Figure cf) at room temperature changes with the polarization voltage applied on PMN-0.29PT (001) substrate.
[0028] Figure 7 GIXRD 2θ scans of Te films prepared under different chamber pressures.
[0029] Figure 8 Surface AFM morphology images of Te films prepared under different chamber pressures.
[0030] Fig. 9 The curves of the resistance of Te films prepared for different cavity gas pressures versus the polarization electric field applied on the PMN-0.29PT (001) substrate.
[0031] Fig.10 GIXRD 2θ scans of Te films prepared at different laser energy densities.
[0032] Fig.11 Surface AFM morphology images of Te films prepared at different laser energy densities.
[0033] Fig.12 The curves of the resistance of Te films prepared at different laser energy densities as a function of the polarization electric field applied on the PMN-0.29PT (001) substrate.
[0034] Fig.13 For PMN-0.29PT substrate in E G = +2kV / cm and E G = -2kV / cm The morphology of the Te film changes when the electric field is alternating. Figure (a) and (d) Scanning electric field E G = Optical microscope images of the sample surface after +2kV / cm and -2kV / cm; Figures (b) and (c) E G = AFM images of a single crack in the Te film after +2 kV / cm and -2 kV / cm; Figures (e) and (f) E G = AFM 3D images of the same crack in the Te film after +2kV / cm and -2kV / cm; Figure (g) Schematic diagram of the switching of 109° domains and 180° domains with positive and negative electric fields.
[0035] Fig.14 GIXRD 2θ images of Te / PMN-0.29PT(001) heterojunctions with film thickness ranging from 50 to 456 nm.
[0036] Fig.15 AFM images of Te / PMN-0.29PT heterostructures with film thickness ranging from 50 to 456 nm.
[0037] Fig.16 AFM images of the surface morphology of films with thickness ranging from 50nm to 456nm.
[0038] Fig.17 The resistance curve of Te films with thickness ranging from 50-456nm and the bipolar electric field applied to PMN-0.29PT at T=300K.
[0039] Fig.18 is the scanning electric field E G = -2kV / cm, optical microscope images of the surface of Te films with thickness ranging from 50 to 456nm.
[0040] Fig.19 (a) A pulse electric field (E) is applied to the PMN-0.29PT (001) substrate. G = ±2 kV / cm, blue curve) to switch the resistivity of the Te film (red curve);
[0041] (b) Repeatability test of resistance switching by pulsed electric field, with pulse amplitude and duration of ±2 kV / cm and 2 s, respectively; the inset in (b) shows a magnified view of the resistance-pulse number curve (from 600 to 1000);
[0042] (c) The different resistance states of Te films are maintained for up to 2 hours. DETAILED DESCRIPTION
[0043] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0044] A. Preparation of Te target
[0045] The instrument is a spark plasma sintering system of Sumitomo SPS-2040 produced in Japan.
[0046] like Figure 1 Shown is a schematic diagram of a spark plasma sintering device.
[0047] Weigh 5g Te powder (99.99%) and put it into a 20mm graphite mold, then put it into the SPS cavity. Then heat it to 658K, apply a pressure of 50MPa, sinter for 8min, then cool it down to room temperature, and take out the sintered target. Finally, scrape off the carbon paper covering the surface of the target, and polish the target with metallographic sandpaper until it is smooth before use.
[0048] Scrape the surface of Te target to obtain powder for XRD diffraction characterization, such as Figure 2 As shown, the diffraction peak of the Te target corresponds to the standard Te-PDF#30-1452 diffraction card, indicating that the target is a one-dimensional spiral chain structure.
[0049] The present invention uses a CuKα1 radiation X-ray diffractometer (SmartLab, Rigaku).
[0050] B. Preparation of Te / PMN-PT heterojunction
[0051] According to the parameters shown in Table 1, a Te film was grown on a (001) oriented and single-sided polished PMN-0.29PT ferroelectric single crystal substrate with a size of 5 mm×5 mm×0.5 mm using pulsed laser deposition technology.
[0052] The PMN-0.29PT single crystal substrate and Te target were placed in the vacuum deposition chamber. When the vacuum degree reached 1×10 -5 After Pa, argon gas at a certain pressure was passed, and a KrF laser (λ=248 nm) was used to ablate the Te target.
[0053] The distance between the target and the substrate is 5 cm, and the laser energy density is set to 1.5-2.5 J / cm 2 , the laser frequency is 5Hz.
[0054] After deposition, the sample was annealed in situ for 1 h and then cooled to room temperature at a rate of 4 °C / min.
[0055] Table 1 Experimental parameters of Te thin films prepared by pulsed laser deposition
[0056]
[0057] B1. Effect of temperature on the structural characterization and performance of Te / PMN-PT heterojunction
[0058] The melting point of Te is 452°C, so 120, 130, 140, and 150°C are selected as deposition temperatures. The specific parameters are shown in Table 2 below:
[0059] Table 2 Parameters of Te thin films prepared at different deposition temperatures
[0060]
[0061] In order to characterize the crystal structure of the film, the influence of the substrate needs to be avoided. Therefore, parallel light grazing incidence was used to characterize the Te / PMN-0.29PT(001) heterojunctions prepared at different deposition temperatures. The GIXRD 2θ scans were measured, as shown in Figure 3 shown.
[0062] like Figure 3 The GIXRD pattern of the film shown contains diffraction peaks in all directions of Te crystals, indicating that Te is a polycrystalline film. As the temperature increases, the main peak position (101) of the tellurium film first increases and then weakens. Among them, the diffraction peak of the film shows a higher intensity and a narrower width when the deposition temperature is 140°C, which means that the crystallinity is the best.
[0063] like Figure 4 Shown are surface AFM morphologies of Te films at different deposition temperatures.
[0064] The scanning electron microscope used in the present invention is a field emission scanning electron microscope produced by Zeiss of Germany, model SUPRA S5SAPPHIRE, which is used to measure the surface morphology and thickness of the film.
[0065] It can be seen that the coarseness of the tellurium films prepared at different temperatures is 2.3nm, 2.5nm, 2.8nm, and 3.5nm, respectively. It can also be seen that with the increase of temperature, the grain size of the deposited film gradually increases, and the surface of the film becomes rougher. Because according to the nucleation thermodynamic theory under non-spontaneous nucleation conditions, as the substrate temperature increases, the critical nucleation particle size of the film decreases, and at the same time, the atomic surface diffusion rate is high, resulting in an increase in grain size.
[0066] like Figure 5 As shown, Figures (a)-(b) are schematic diagrams of the internal polarization direction of PMN-0.29PT when the substrate is in positive and negative polarization states, respectively.
[0067] According to the measurement schematic diagrams shown in Figures (a) and (b), an electric field was applied along the thickness direction of PMN-PT at room temperature, and the resistance of the film was measured simultaneously. The scanning electric field program was: 0→-4→0→+4→0 (kV / cm).
[0068] When the electric field gradually increases from 0 kV / cm to -4 kV / cm, the substrate is in a negative polarization state (Pr-).
[0069] In contrast, when the electric field increases from 0 kV / cm to +4 kV / cm, the substrate becomes positively polarized (Pr+).
[0070] like Figure 6 As shown, Figures (c)-(f) are the curves of the resistance of Te films grown at different deposition temperatures at room temperature as a function of the polarization voltage applied on the PMN-0.29PT (001) substrate.
[0071] Figures (c)-(f) show that the RE curves of Te films grown at different deposition temperatures all present a rectangular shape similar to the substrate hysteresis loop. When the substrate is in a positive polarization state, the film resistance decreases; when the substrate is in a negative polarization state, the film resistance increases.
[0072] At the same time, the deposition temperature will affect the resistance of the film and the relative change of resistance. When the temperature ranges from 120℃ to 140℃, the film resistance is 2.8kΩ, 6.4kΩ, 8.6kΩ and 8kΩ respectively. As the temperature increases, the film resistance increases first and then decreases. The resistance of the film when the substrate is in a completely positive polarization state is defined as R(Pr-), and the resistance when it is in a completely negative polarization state is defined as R(Pr+). Then, the relative change in the room temperature resistance of the film sample caused by the reversal of the polarization direction of the PMN-PT substrate can be calculated. ΔR / R=[R(Pr-)-R(Pr+)] / R(Pr+). Among them, when the substrate temperature is 140℃, the film resistance change curve caused by the substrate polarization reversal is relatively smooth, the data has no obvious jitter, and the relative resistance is the highest, reaching 32643%.
[0073] In summary, the tellurium thin film prepared at a substrate temperature of 140°C has good crystallization, a smooth surface, and the largest control range, so the optimal deposition temperature is determined to be 140°C.
[0074] B2. Effect of cavity pressure on the structural characterization and performance of Te / PMN-PT heterojunction
[0075] When depositing thin films, a background atmosphere of a certain pressure is usually introduced into the chamber to promote the formation of crystal nuclei and the growth of grains. Considering that tellurium is a non-oxide, argon gas, which does not participate in the reaction, is selected to control the deposition rate of the film and improve the film quality.
[0076] The deposition pressure was set to 0.2Pa, 0.8Pa, and 5Pa, respectively, and Te thin films were grown on PMN-0.29T (001) substrates. The specific growth parameters are shown in Table 3 below:
[0077] Table 3 Parameters of Te thin films prepared at different deposition temperatures
[0078]
[0079] like Figure 7 Shown are GIXRD 2θ scans of Te films prepared under different chamber pressures.
[0080] It can be seen that with the increase of cavity pressure, the half-width of the (101) diffraction peak decreases, the crystallization performance of the film improves, and the grain size becomes larger.
[0081] like Figure 8 Shown are the surface AFM morphologies of Te films under different cavity pressures.
[0082] It can be seen that the grain size of the film increases with the increase of deposition pressure, which is consistent with the XRD test results. In addition, the surface roughness of the film is 2.6nm, 2.7nm, 2.8nm, and 27.6nm, respectively; indicating that as the grain size in the film gradually increases, the surface of the film gradually becomes rough. This is because as the deposition pressure increases, the probability of collision between sputtered atoms and argon atoms increases, the deposition rate decreases, and the sputtered atoms have enough time to migrate on the substrate surface, which is conducive to the formation of nuclei and the increase of grain size.
[0083] like Fig. 9 , which is a curve showing the change of the resistance of Te thin films prepared with different cavity gas pressures with the polarization electric field applied on the PMN-0.29PT (001) substrate.
[0084] It can be seen that the deposition pressure affects the resistance of the film and the relative change of resistance. -5 Pa to 5Pa, the film resistance is 29kΩ, 33kΩ, 8.6kΩ and 7.25kΩ respectively. With the increase of the cavity pressure, the film resistance increases and then decreases. When the cavity is in a high vacuum, the relative resistance of the film is the largest, reaching 50691%. When argon gas is introduced into the cavity, the change amplitude and stability of the film resistance with the applied electric field are reduced.
[0085] In summary, the deposition pressure is 1×10 -5 Pa, the film surface is the smoothest and the electric field has the largest control over the film resistance. Therefore, the optimal deposition pressure is determined to be 1×10 -5 Pa.
[0086] B3. Effect of laser energy density on the structural characterization and performance of Te / PMN-PT heterojunction
[0087] If the laser energy is too low, the kinetic energy of the sputtered atoms is low, the surface mobility is small, and the film tends to grow in an island-like pattern; if the laser energy density is too high, the kinetic energy of the high-energy particles during sputtering is too large, and they are easily reflected after contacting the substrate, which is not conducive to the growth of the film.
[0088] Therefore, four different laser energy densities were selected to prepare Te thin films, and the parameters of film growth are shown in Table 4:
[0089] Table 4 Parameters of Te thin films prepared at different deposition temperatures
[0090]
[0091] like Fig.10 Shown are GIXRD 2θ scans of Te films prepared at different laser energy densities.
[0092] It can be seen that with the increase of laser energy density, the diffraction peak of the film becomes wider and wider, the crystallization performance of the film becomes worse, and the grains become smaller.
[0093] like Fig.11 Shown are surface AFM morphologies of Te films prepared at different laser energy densities.
[0094] It can be seen that the film surface roughness is 2.6nm, 2.5nm, 2.4nm, and 2.3nm, respectively. That is, as the energy density increases, the film surface becomes smoother and smoother. This is because as the laser energy density increases, more sputtered atoms are firmly adsorbed on the substrate surface, connected into one piece, and grow in two-dimensional layers, so the film surface becomes smoother.
[0095] like Fig.12 As shown, the resistance curve of Te thin films prepared at different laser energy densities varies with the polarization electric field applied on the PMN-0.29PT (001) substrate.
[0096] Laser energy density affects the resistance of the film and the relative change of resistance. Energy density ranges from 1.5-2.5J / cm 2 The film resistance values are 15kΩ, 29kΩ, 120kΩ and 150kΩ respectively. With the increase of laser energy density, the film resistance shows an increasing trend.
[0097] At the same time, the resistance curves of all film samples measured with electric field showed a rectangular shape similar to the hysteresis loop of the substrate. It can be seen that the energy density is 1.5J / cm 2 , the RE curve is the smoothest, and the relative resistance of the film is the largest, reaching 13856%. Moreover, after the electric field is removed, the tellurium film still maintains a stable high and low resistance state.
[0098] In summary, the energy density is 1.5 J / cm 2 When the electric field has the largest control over the film resistance, the optimal energy density is determined to be 1.5 J / cm 2 .
[0099] Therefore, by using pulsed laser deposition technology, through the characterization of thin film structures grown at different deposition temperatures, deposition pressures and laser energy densities and preliminary analysis of electric field regulation, a tellurium polycrystalline thin film growth process with high quality, excellent performance and large-scale non-volatile regulation was determined, as shown in Table 5 below:
[0100] Table 5 Optimal parameters for preparing Te thin films
[0101]
[0102] C. Regulation of the physical properties of Te / PMN-PT heterojunction by electric field
[0103] The surface morphology of the film under positive and negative polarization states of the substrate was observed using an optical microscope and AFM. Fig.13 As shown, PMN-0.29PT substrate in E G = +2kV / cm and E G = -2kV / cm The morphology of the Te film changes when the electric field is alternating.
[0104] Figures (a) and (d) show the scanning electric field E G = Optical microscope images of the sample surface after +2kV / cm and -2kV / cm;
[0105] Figures (b) and (c) are E G = AFM images of a single crack in Te film after +2 kV / cm and -2 kV / cm;
[0106] Figures (e) and (f) are E G = AFM 3D images of the same crack in Te film after +2kV / cm and -2kV / cm;
[0107] Figure (g) is a schematic diagram of the switching of 109° domain and 180° domain with positive and negative electric fields.
[0108] It can be seen that there are significant differences in the surface morphology of Te films when the substrate is in the positive polarization state and the negative polarization state.
[0109] Fig.13 (a) and (d) clearly show the large-scale opening and closing of cracks on the film surface.
[0110] The width of the crack was scanned using AFM. Fig.13 (b) and Fig.13 As shown in (c), a negative electric field (E G =-2kV / cm), the cracks on the surface of the Te film opened with a height difference of 822nm, corresponding to the high resistance state in the resistance measurement; when the external electric field was +2kV / cm, the surface cracks of the film closed with a height difference of 100nm, corresponding to the low resistance state in the resistance measurement. G = +2kV / cm to -2kV / cm, the crack depth is much greater than the roughness of the film (1.5nm).
[0111] This indicates that the crack is caused by the strain at the interface transferred from the ferroelectric substrate to the film, not by the uneven film deposition. AFM micro-area scanning also shows that the height difference between the two sides of the crack increases by about 700nm as the substrate switches from +2kV / cm to -2kV / cm.
[0112] In order to describe the motion of ferroelectric domains, a simplified two-domain configuration (r2+ and r4+) is used. Fig.13 As shown in (g), when the electric field changes from +2→-2→-4 (kV / cm), the ferroelectric domains switch 109° (r2+ to r3- or r4+ to r1-) and 180° (r2+ / r4+ to r2- / r4-) sequentially.
[0113] The present invention selects E G = ±2kV / cm as a pulsed electric field, causing most ferroelectric domains to switch 109°. When the electric field is -2kV / cm, the ferroelectric domains flip 109° to generate in-plane tensile strain in the PMN-0.29PT ferroelectric layer, and then the in-plane tensile strain is transmitted to the film through the interface, forming cracks on the film surface, and the film changes from a low resistance state to a high resistance state. When the electric field is scanned to +2kV / cm, the 109° domain switches to
[0114] <111> direction, the tensile strain parallel to the surface disappears in the ferroelectric layer, there is no strain at the interface between the substrate and the film, the open cracks close, and the film is again in a low-resistance state with good conductivity.
[0115] The different states of the cracks in positive and negative fields are caused by the asymmetric reversal of the domains with respect to the electric field direction. Since the E-induced 109° polarization switching is reversible and nonvolatile, the induced crack and resistance switching should also be reversible and nonvolatile.
[0116] D. Effect of Thickness on Nanomechanical Cracks and Resistance in Te / PMN-PT Heterojunctions
[0117] By changing the deposition time, four tellurium films of different thicknesses were studied. The structures of the four films were characterized and the electric field was controlled to summarize the effect of thickness on the formation of reversible cracks. The specific parameters of the film preparation are shown in Table 6 below.
[0118] Table 6 Parameters for preparing Te films with different thicknesses
[0119]
[0120] like Fig.14 The following are GIXRD 2θ images of Te / PMN-0.29PT(001) heterojunctions with film thickness ranging from 50 to 456 nm. It can be seen that the thinner the prepared Te polycrystalline film, the better the crystallinity.
[0121] like Fig.15 The following are AFM images of Te / PMN-0.29PT heterostructures with film thickness ranging from 50 to 456 nm, indicating that the film thicknesses are 50 nm, 93 nm, 167 nm, and 456 nm, respectively.
[0122] like Fig.16The following are AFM images of the surface morphology of films with thicknesses ranging from 50nm to 456nm. By scanning the surface morphology of the films, it is found that the roughness of the films is 1.5nm, 2.0nm, 2.7nm, and 3.0nm, respectively, indicating that the thicker the film, the greater the surface roughness.
[0123] like Fig.17 As shown, the electric field of the four-thickness film is controlled by scanning the gate electric field (E G ) while measuring the resistance of the Te film. The resistance vs. electric field curves of all film samples showed a rectangular shape similar to the hysteresis loop of the substrate. It is obvious that R(ON) / R(OFF) decreases with increasing thickness. As the thickness of the film increases from 50nm to 456nm, the transfer of in-plane tensile strain in the PMN-0.29PT layer to the film surface becomes increasingly challenging. Optical observations of the film surface, such as Fig.18 As shown, when the electric field is -2kV / cm, the cracks on the film surface become more and more blurred as the thickness increases.
[0124] Therefore, as the film becomes thicker, the resistance in the "OFF" state and the on / off ratio decreases.
[0125] In summary, the Te film with a thickness of 50 nm has high quality, and the prepared Te / PMN-0.29PT heterojunction has the largest relative resistance change.
[0126] Device stability and fatigue resistance of E.Te / PMN-PT heterojunction
[0127] A 50nm-thick Te / PMN-PT heterojunction was selected for repeatability testing, and the results are shown in Fig.19 As shown in (a), the resistance of the film is measured while applying a pulsed electric field of ±2kV / cm to the substrate at a time interval of 2s. The results show that positive polarization corresponds to a low-resistance "ON" state, while negative polarization corresponds to a high-resistance "OFF" state. After the electric field is removed, the resistance of the Te film remains stable and non-volatile. And the "OFF" state exceeds the measurement limit (straight line state), indicating that the leakage current can be ignored when the crack is open. Therefore, the ideal state of ultra-low standby power can be achieved, meeting the requirements of minimum power consumption.
[0128] Fig.19 (b) The resistance of the film is measured as a function of the number of applied pulses. It can be seen from this figure that the crack can be opened and closed reversibly for more than 1,000 times.
[0129] Fig.19 (c) shows that after the polarizing electric field is removed, the “ON” and “OFF” states remain stable for more than 2 h.
[0130] In summary, it is demonstrated that the device has excellent stability, durability and fatigue resistance, and can be applied to memory devices.
[0131] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A reversible nanocrack film, characterized in that: A 50 nm thick tellurium film deposited on a PMN-PT (001) ferroelectric single crystal substrate induces a 109° ferroelectric domain flip by an electric field, causing the nanocracks on the surface of the tellurium film to reversibly open and close.
2. The reversible nanocrack film according to claim 1, characterized in that: The electric field is the field strength E G = Pulsed electric field of ±2kV / cm.
3. A method for preparing a reversible nanocrack film, characterized in that: A tellurium film was deposited and grown on a PMN-0.29PT ferroelectric single crystal substrate using a pulsed laser precipitation method to form a reversible nanocrack film with a "Te film / PMN-0.29PT" structure.
4. The preparation method according to claim 3, characterized in that: The size of the PMN-0.29PT ferroelectric single crystal substrate is 5 mm×5 mm×0.5 mm; the laser energy density of the pulsed laser precipitation method is 1.5 J / cm 2 ; The deposition temperature is 140°C and the deposition pressure is 1×10 -5 Pa.
5. Use of the reversible nanocrack film according to any one of claims 1 to 4 as a nanocrack switch.
6. Use of the nanocrack switch according to claim 5 in a non-volatile memory.